Astragalus membranaceus Injection Suppresses Production of Interleukin-6 by Activating Autophagy through the AMPK-mTOR Pathway in Lipopolysaccharide-Stimulated Macrophages. (7th July 2020) - Zhang, Xiaoyan; Liang, Taigang; Yang, Wanxia; Zhang, Lanfang; Wu, Shuting; Yan, Chaoqun; Li, Qingshan
Abstract : Astragalus membranaceus (AM), used in traditional Chinese medicine, has been shown to enhance immune functions, and recently, its anti-inflammatory effects were identified. However, the mechanisms of action remain unclear. Most studies have shown that autophagy might be involved in the immune response of the body, including inflammation. Here, we developed an inflammatory model by stimulating macrophages with lipopolysaccharides (LPS) to explore the anti-inflammatory effect and mechanisms of AM injection from the perspective of the regulation of autophagy. Immunoblot, immunofluorescence, and ELISA were used to determine the effects of AM injection on the production of interleukin-6 (IL-6) and alterations of autophagy markers. It was found that AM injection reduced the expression of IL-6 in LPS-stimulated macrophages and reversed the LPS-induced inhibition of cellular autophagy. After treatment with inhibitors of signaling pathways, it was shown that LPS downregulated autophagy and upregulated the production of IL-6 in macrophages via the protein kinase B (Akt)/mammalian target of rapamycin (mTOR) pathway. AM injection reversed the effects of LPS by activating the AMP-activated protein kinase (AMPK) instead of inhibiting Akt. These results were further confirmed by testing activators and siRNA silencing of AMPK. Hence, these 2 distinct signaling molecules appear to exert opposite effects on mTOR, which integrates information from multiple upstream signaling pathways, negatively regulating autophagy. In addition, we demonstrated that autophagy might play a key role in regulating the production of IL-6 by testing activators and inhibitors of autophagy and siRNA silencing of ATG5 . These findings showed that AM injection might enhance autophagy by activating AMPK and might further play a repressive effect on the LPS-stimulated expression of IL-6. This study explored the relationship between autophagy, signaling pathways, and the production of inflammatory factors in a model of endotoxin infection and treatment with AM injection.